2017
DOI: 10.3389/fneur.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

Flow Diversion for the Treatment of MCA Bifurcation Aneurysms—A Single Centre Experience

Abstract: BackgroundIntracranial aneurysms located at the bifurcation of the middle cerebral artery (MCA) can often be challenging for the neurointerventionalist. We aimed to evaluate the efficacy and safety of flow diverting stents (FDS) in the treatment of these aneurysms.Materials and methodsWe retrospectively reviewed our prospectively maintained database to collect information for all patients with unruptured saccular bifurcation MCA aneurysms treated with FDS between January 2010 and January 2016. In addition to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 52 publications
2
43
0
2
Order By: Relevance
“…Overall, 22 included studies were retrospective series, 1,2,4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] whereas 5 articles were prospective series (details in On-line Table 3). [29][30][31][32][33]…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…Overall, 22 included studies were retrospective series, 1,2,4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] whereas 5 articles were prospective series (details in On-line Table 3). [29][30][31][32][33]…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…Overall, previous series have reported a rate of complete/near-complete occlusion between 60% and 90% after flow-diversion treatment of MCA aneurysms. [5][6][7][8][9][12][13][14]20 The paucity of large and prospective studies, the heterogeneity of the reported populations, and the relatively short follow-up periods can explain this variation. Our study, the largest to date, demonstrated that the overall rate of complete/near-complete occlusion is roughly 80% during a mean follow-up of 14 months.…”
Section: Angiographic Outcomes Of Mca Aneurysms After Flow Diversionmentioning
confidence: 99%
“…1 Recently, flow diversion has been used as an alternative technique for complex wide-neck MCA aneurysms, incorporating Ն1 side branch or in cases of previous endovascular or surgical failure. [5][6][7][8][9][10][11][12][13][14] However, the role of flow diversion in this location is controversial, and the efficacy and safety of this technique remain unclear. We performed a systematic review and meta-analysis of all published series examining flow diversions for the treatment of MCA aneurysms with the aim of clarifying the following: 1) aneurysm occlusion rate, 2) treatment-related complications and clinical outcome, and 3) the fate of the MCA side branch covered with the device.…”
mentioning
confidence: 99%
“…Hence, a subsidiary endovascular approach, flow diversion (FD), was introduced to further enhance endovascular aneurysm therapy ( 5 ). FD has been established as a successful technique to neutralize wide-neck sidewall aneurysms with saccular configuration, selected bifurcation aneurysms, fusiform aneurysms, and dissecting aneurysms of the intracranial circulation ( 6 12 ). FD uses devices with significantly increased material coverage in comparison with conventional stents, aiming to reconstruct the parent vessel whilst excluding the aneurysm from the circulation ( 5 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%